فعالية الاتصال في المكتبات الجامعية وعلاقته بتسهيل عملية البحث العلمي - • العقون أسماء ريان; حبيش عائشة; - المداني حجاج (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة: ملخص العربية تكلم هذهالدراسة حول مساهمة فعالية الاتصال في تسهيل عملية البحث فهوموضوع مهميجمع ثلاث مصطلحاتالاتصال وهو مسير لأي مؤسسة والمنظم لها و المكتبات الجامعية المغذي العلمي للجامعات والداعم المعلوماتي للبحوثو كذا البحث العلمي الذي يعتبر الوسيلة التي توفسر بها الظواهر وتكشف عن طريقها الحقائق والوصول إلى نتائج المراد تحققها وبهذا نقول انمساهمة المكتبات الجامعية فينجاح البحوث العلمية عن طريق توجيهه الباحث وتوفير كل مايحتاجه من مصادر المعلومات. ومنه طرح التساؤل الرئيسي وهو -مامدى مساهمة فعالية الاتصال في تسهيل عملية البحث العلمي؟الاتصال تعتمد علىقوته المكتبات في القيامبأعمالها فهو يسيرها وينظمها ويضمن بقائها. ومن جهة أخرى الباحثين اثناء إجراءالبحث العلمي يعتمدون على المكتبات الجامعية في تحقيق أهداف علمية فهي توفرالخدمات اللازمة لهم .وهكذا نقول الاتصال يخدم المكتبة والمكتبة بدورها تخدم عملية البحث العلمي. سعت دراسة إلى وصول إلى مدى مساهمة فعالية الاتصال في تسهيل عملية البحث العلمي. تكلمت عن الاتصال والمكتبات بشكل عامكما تضمنت الدراسة فرضية رئيسية وفرضيتان جزئيتان وهي كالأتي: -يساهم الاتصال في عملية البحث العلمي بمكتبة المركزية بجامعة. 1- تقدم المكتبة كل متطلبات البحث العلمي 2- يساهم الاتصال بقدر كبير في المكتبة المركزية بجامعة الأغواط. جاء في الدراسة اربع فصول اول فصل كان عبارة عن المنهجية اما الفصل الثاني تناول الاتصال أهمية اهداف مهارات مبادئ معوقات التي تواجهه وطرق علاجها والفصل الثالث تطرق إلى المكتبات الجامعية أنواعها أهميتها اما الفصل الرابع وهو الإطار الميداني الذي احتوى على منهج الدراسة وهو منهج الوصفي والعينة التي وقع عليها الاختيار هي العينة القصدية حيث يمثل عددأفرادها50 طالب يترددون على المكتبة المركزية بجامعة الأغواطوأداة جمع بيانات الدراسة وهي الاستبيان وبعد توزيع الاستبيان وتحليل معطيات توصلنا الى مجموعة من النتائج على ضوء فرضيات وهي على شكل الاتي: - تقدم المكتبة كل ما يحتاجه الطلاب في عملية البحث العلمي . -الاتصال له دور فعال في تسهيل عملية البحث العلمي ومساعدتهم في كل متطلبات بحوثهم العلمية نذكر جملة من نتائج الدراسة: -هناك معوقات تصادف الطلاب في اقتناء مصادر المعلومات.. -المكتبيون في المكتبة المركزية بجامعة الأغواط يتعاملون مع طلاب بشكل جيد. -المكتبة المركزية بجامعة الأغواط تعاني من نقص في كتب والمراجع. -الاتصال له دور فعال في تسهيل عملية البحث العلمي. ملخص بالانجليزية: Summary: This study focuses on the contribution of effective communication in facilitating the research process. It is an important topic that combines three terms: communication, which is the backbone of any organization and its organizer, university libraries, the scientific nourishment of universities, and the information support for research. Additionally, scientific research is considered the means through which phenomena are explained, facts are revealed, and desired results are achieved. Thus, the contribution of university libraries in the success of scientific research by guiding researchers and providing them with the necessary information sources is emphasized. The main question posed is: To what extent does effective communication contribute to facilitating the scientific research process? Communication relies on the strength of libraries in carrying out their work, managing them, and ensuring their sustainability. On the other hand, researchers rely on university libraries to achieve their scientific goals as these libraries provide the necessary services for them. Therefore, it can be said that communication serves the library, and the library, in turn, serves the scientific research process. The study aimed to determine the extent of the contribution of effective communication in facilitating the scientific research process. It discussed communication and libraries in general. The study included a main hypothesis and two sub-hypotheses as follows: - Communication contributes to the scientific research process at the central library of the university. - The central library at the University of Agouat contributes significantly through effective communication. - The study consisted of four chapters. - The first chapter covered the methodology, while the second chapter addressed the importance, objectives, skills, principles, and obstacles of communication, as well as ways to overcome them. - The third chapter focused on university libraries, their types, and their significance. - The fourth chapter presented the field framework, including the descriptive methodology and the selected sample, which consisted of 50 students who frequented the central library at the University of Agouat. - The data collection tool used was a questionnaire. After distributing the questionnaire and analyzing the data, several results were obtained based on the hypotheses, including: - The library provides everything students need in the scientific research process. Communication plays an active role in facilitating the scientific research process and assisting students in all their scientific research requirements. Some notable study findings were: - Students face obstacles in acquiring information sources. - The librarians at the central library of the University of Agouat deal well with students. - The central library at the University of Agouat suffers from a shortage of books and references. - Communication plays an active role in facilitating the scientific research process.
- دراسة ميدانية بالمكتبة المركزية بجامعة الاغواط